Feasibility Study of PT XYZ's Villa Project In Seminyak, Bali - Wijaya, Darren Anthony; Kitri, Mandra Lazuardi (Journal Integration of Management Studies, 2024)
The tourism industry in Bali, a cornerstone of the local economy, faced a severe downturn due to COVID-19, resulting in declines in tourist arrivals and accommodations. However, the sector has seen a robust recovery, with tourist arrivals now exceeding pre-pandemic levels. Despite this, accommodations recovery has lagged, presenting a significant investment opportunity. PT XYZ aims to capitalize on this by developing a luxury villa in Seminyak, targeting the middle-to-upper tourist market. The planned investment of IDR 2,109,848,475 will be fully financed through equity. This study assesses the financial feasibility and potential risks of the project. It involves constructing pro forma financial statements to forecast operations over 20 years, followed by detailed cash flow analysis. Key metrics such as Free Cash Flow (FCF) and Terminal Cash Flow are calculated, and the Weighted Average Cost of Capital (WACC) is used to discount future cash flows. The analysis employs Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Payback Period, and Discounted Payback Period to evaluate financial returns and investment recovery time. The study indicates a positive NPV of IDR 1.6 billion and an IRR of 19.36%, suggesting substantial returns over the cost of capital. The project’s profitability index of 1.77 underscores its value generation potential, while the payback period and discounted payback period, at 6.06 years and 9.07 years respectively, highlight its efficiency in recouping investments well within its useful life. Risk assessment through sensitivity analysis and Monte Carlo simulations highlights daily and occupancy rates as critical factors, with a low 4.5% probability of a negative NPV. Strategic recommendations include dynamic pricing, enhancing guest experience with exclusive amenities, and listing the property on multiple Online Travel Agencies (OTAs) to boost visibility and bookings.